Using boolean algebra, simplify each expression:
_
(B + BC)(B + B^C)(B + D)
AB + A'C + B'C
= AB + A'BC + A'B'C + B'C
= AB + A'BC + B'C (1 + A')
= AB + A'BC + B'C
= ABC + ABC' + A'BC + B'C
= BC(A+A') + ABC' + B'C
= BC + B'C + ABC'
= C + ABC'
I have a second question, might as well add it here because it's also simplification of boolean algebra.
f = cx + ac'x + bc'x + a'b'c'x' (used a K-map to generate this, now I have to simplify further)
f = c'x(a+b) + cx + a'b'c'x' - no idea how to continue from here
Comments
Leave a comment